To find the nth term of a sequence, we first need to identify the pattern or rule governing the sequence. In this case, the sequence appears to be increasing by 9, then 13, then 17, and so on. This pattern indicates that the nth term is given by the formula n^2 + n - 1. So, the nth term of the sequence 0, 9, 22, 39, 60 is n^2 + n - 1.
Un = 4n - 68
60/88 = 30/44 = 15/22
60-39=21.
65% 39/60, *100
7h+39=60 Take away 39 from both sides (called isolating your variable) 7h=21 Divide by seven, because (I assume) you are looking for h, not 7h h=3 And to check: 7(3)+39=60 21+39=60 60=60
Un = 4n - 68
55 + 5N or 60 + 5(N - 1)
720
2n(n+1)
60/88 = 30/44 = 15/22
15
go ask your teacher and tell him hes dumb
39 out of 60 = 39 / 60 = 0.65Converting decimal to a percentage: 0.65 * 100 = 65%
60-39=21.
39 out of 60 = 39 / 60 = 0.65Converting decimal to a percentage: 0.65 * 100 = 65%
39 x 60 = 2,340
39/60 = 65%